Chlamydia Trachomatis Genital Infections among Portuguese Adolescents - Vaz Pereira, Francisco (2020)
Adolescents (between 10 and 19 years old) are an age group with a high prevalence of sexually transmitted infections (STI), due to biological and socio-behavioural factors. In Portugal, adolescents show poor condom adherence, have multiple sexual partners, poor sex education and high reinfection rates. In this age group, genital infection by Chlamydia trachomatis is the most prevalent STI, whose asymptomatic course makes diagnosis and epidemiological control difficult. The aim of this study is to review the published data on prevalence of genital infection by Chlamydia trachomatis in Portuguese adolescents. In the Portuguese population studies, which are highly heterogeneous, a prevalence of between 2.23%-18.2% was found. Portuguese notification rates are lower than in other European countries. Moreover, national official data do not discriminate adolescents in their age ranges. Between 15-24 years old, 41 cases were identified in 2015 and 56 cases in 2016. According to the European Center for Disease Control, 116 and 167 cases from this age group were reported in Portugal in 2017 and 2018, respectively. Understanding the epidemiology of genital CT infection in Portuguese adolescents is almost impossible due to underdiagnosis, underreporting and non-isolation of adolescents in studied groups. A concerted effort at clinical and political level is therefore needed to devise an effective strategy to combat this infection in adolescents.